VELU THAMPI DALAWA AND HIS INVALUABLE CONTRIBUTIONS TO TRAVANCORE HISTORY: A RE- READING - SHAMBU R
The role of Dalawas in the making of Kerala history and especially that of Travancore history is a relevant study in itself. Mostly, these ministerial position or those who adorned this position were subservient towards their rulers having complete allegiance and faith in the ruling authority. Velu Thampi Dalawa however was an insult to this particular practice as he was a strong willed man with his own personal decisions and administrative skills. Travancore at that point of time was under resident rule of British with the ruler of Travancore being made a puppet in the hands of an alien rule. Velu Thampi held his own visions for state development and its subsequent administration. He understood that the British were exploiting Travancore completely in the name of Resident rule. He raised his voice against them assimilated people through well known activities such as kundara proclamation allied with his contemporaries such as palieth Achan etc. and initiated fight against alien domination and exploitation. Even though the struggle ended up in favour of British his patriotic activities and fight against British especially from south Indian division still remains as an unforgettable chapter in the history of Travancore and Kerala.